2015
DOI: 10.1016/j.rmed.2014.07.021
|View full text |Cite
|
Sign up to set email alerts
|

Non cystic fibrosis bronchiectasis: A longitudinal retrospective observational cohort study of Pseudomonas persistence and resistance

Abstract: P. aeruginosa is associated with greater persistent infection rates and more hospital admissions than H. influenzae. Exacerbation rates, however, were similar; therefore H. influenzae causes significant out-patient morbidity. P. aeruginosa infection occurs across all strata of lung function impairment but is infrequently multi-resistant in bronchiectasis. Careful microbiology follow up is required even in those with well-preserved lung function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
113
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 122 publications
(129 citation statements)
references
References 35 publications
6
113
1
2
Order By: Relevance
“…However, no colonization with pathogens was detected in either of the patients with BE who died. McDonnell and colleagues reported that there was no relationship between colonization of P. aeruginosa and exacerbation rate in patients with BE (29). According to these data, MPA patients with BE had higher mortality rates due to respiratory infection in the late phase, even if the patients had not been colonized by any pathogens.…”
Section: Discussionmentioning
confidence: 97%
“…However, no colonization with pathogens was detected in either of the patients with BE who died. McDonnell and colleagues reported that there was no relationship between colonization of P. aeruginosa and exacerbation rate in patients with BE (29). According to these data, MPA patients with BE had higher mortality rates due to respiratory infection in the late phase, even if the patients had not been colonized by any pathogens.…”
Section: Discussionmentioning
confidence: 97%
“…In keeping with recommendations in cystic fibrosis, most specialist bronchiectasis centres will attempt eradication of P. aeruginosa upon first isolation [2]. Retrospective studies reporting high rates of P. aeruginosa eradication with treatment must be interpreted in light of data that suggests spontaneous clearance of P. aeruginosa occurs frequently in bronchiectasis both in clinical practice and in the placebo arms of randomized controlled trials [90,91]. Therefore the authors will typically perform a second sputum sample pre-treatment before commencing eradication [2] The BTS guidelines provides a useful algorithm for P. aeruginosa eradication [2].…”
Section: Eradicationmentioning
confidence: 99%
“…P. aeruginosa colonisation defines a specific clinical phenotype of bronchiectasis, and is associated with a three-fold increase risk of death, a nearly seven-fold increase risk of hospital admissions, worse quality of life and more frequent exacerbations [27][28][29]. Evidence from CF suggests that attempts at eradication therapy targeting Pseudomonas can have success in converting patients to culture-negative status [30].…”
Section: Important Research Priorities Identified By Expertsmentioning
confidence: 99%
“…The role of NTM, between innocent colonisers or those causing chronic infection, and the predisposing factors to this need to be differentiated. There is also a paucity of data regarding the isolation of viruses and multiresistant bacteria [4,18,29]. The EMBARC registry is currently collecting susceptibility patterns of bacteria causing chronic infection in patients with bronchiectasis and these data will be crucial in planning further interventional studies on antibiotics at the European level [10].…”
Section: Consensus Statementmentioning
confidence: 99%